Integrated distribution system and urban district planning with high renewable penetrations. Issue 5 (27th February 2019) - Doubleday, Kate; Hafiz, Faeza; Parker, Andrew; Elgindy, Tarek; Florita, Anthony; Henze, Gregor; Salvalai, Graziano; Pless, Shanti; Hodge, Bri‐Mathias
Abstract : Recent efforts to reduce energy consumption and greenhouse gas emissions have resulted in the development of sustainable, smart districts with highly energy efficient buildings, renewable distributed energy resources (DERs), and support for alternative modes of transportation. However, there is typically little if any coordination between the district developers and the local utility. Most attention is paid to the district's annual net load and generation without considering their instantaneous imbalance or the connecting network's state. This presents an opportunity to learn lessons from the design of distribution feeders for districts characterized by low loads and high penetrations of DERs that can be applied to the distribution grid at large. The aim of this overview is to summarize current practices in sustainable district planning as well as advances in modeling and design tools for incorporating the power distribution system into the district planning process. Recent developments in the modeling and optimization of district power systems, including their coordination with multi‐energy systems and the impact of high penetration levels of renewable energy, are introduced. Sustainable districts in England and Japan are reviewed as case studies to illustrate the extent to which distribution system planning has been considered in practice. Finally, newly developed building‐to‐grid modeling tools that can facilitate coordinated district and power system design with utility involvement are introduced, along with suggestions for future research directions. This article is categorized under: Wind Power > Systems and Infrastructure Energy Policy and Planning > Systems and Infrastructure Energy Efficiency > Systems and Infrastructure Abstract : Engaging the local utility and including electrical distribution system design in district master planning can reduce costs and improve performance of sustainable urban districts with high penetrations of renewable energy, but new research tools are needed to facilitate an integrated design. Source : fujisawasst.com/EN /.